Assessing Halal Investment Sensitivity to Cash Flow and the Impact of Capital Market Imperfections: The Case of Asian Countries - Elseoud, Mohamed Sayed Abou (Economica: Jurnal Ekonomi Islam, 2023)
The study empirically examines the relationship between Halal investment sensitivity and the cash flow, as well as the effect of capital market imperfections on sukuk-dependent enterprises in selected non-financial listed companies of the stock markets in six countries, which are Bahrain, KSA, UAE, Kuwait, Qatar, and Malaysia. The study adopts fixed effect model and conducted over the period of 2018-2022 for 240 non-financial listed companies on the stock markets. The study findings show that at the 5% level, cash flow has a significant and positive effect on investment sensitivity in both conventional and Islamic enterprises, where the coefficients of cash flows were 0.176 and 0.143, respectively; this means the effect is significantly greater in conventional enterprises that are more constrained. The coefficients of fund flows, institutional ownership, and the index of corporate governance variables have a significant and negative effect on the sensitivity of investment to cash flow in both types of enterprises. When these variables increase, the sensitivity of investment to cash flow will diminish due to decreasing in capital market imperfections. The implication of this study may help beneficiaries in making better policy decisions and provide guidance for corporate managers.